The influence of e-wom on instagram, destination image and domestic tourist satisfaction on the intention to revisit Jakarta aquarium and safari - Christina Obelia Widodo; Ida Bgs Gede Agung Widana; Dewa Ayu Nyoman Aridayanti (Journal of Tourism and Economic, 2023)
This study aims to determine the partial and simultaneous influence between E-WOM on Instagram, destination image and domestic tourist satisfaction with the intention to revisit Jakarta Aquarium and Safari. This study used multiple linear regression analysis techniques with purposive sampling techniques totaling 130 samples, which the samples were domestic tourists who had visited Jakarta Aquarium and Safari at least 2x. The results of this study show that there is a positive and significant influence of E-WOM on Instagram on the intention to revisit the Jakarta Aquarium and Safari and shows that there is a positive and significant influence of the image of the destination on the intention to revisit the Jakarta Aquarium and Safari. However, there was no significant effect of domestic tourist satisfaction on the intention to revisit the Jakarta Aquarium and Safari. In addition, the results of this study show that there is a positive and significant influence of E-WOM on Instagram, destination image and domestic tourist satisfaction together on the intention to visit Jakarta Aquarium and Safari again. With the coefficient of determination (R-Square) is 27.8% of the intention to visit Jakarta Aquarium and Safari is influenced by E-WOM on Instagram, destination image and domestic tourist satisfaction.